THE INFLUENCE OF COMPETENCE, WORK MOTIVATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE IN THE BATAM CITY GOVERNMENT - Ramadhan, Denny Ammari; Purwaningrum, Ajeng Handayani (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2025)
Competence, work motivation and work discipline variables are the right variables to influence employee performance in the Batam City Government. This research is a quantitative descriptive study with a population and sample of 67 people and the sampling technique is census. Data analysis using AMOS path analysis. From the results of the study it can be concluded that the variables of competence, work motivation and work discipline are the right independent variables in this study in measuringemployee performance.Keyword: Competence, Work Motivation, Work Discipline, Employee Performance